Connexin-43 Gap Junctions Are Responsible for the Hypothalamic Tanycyte-Coupled Network - Recabal, Antonia; Elizondo-Vega, Roberto; Philippot, Camille; Salgado, Magdiel; López, Sergio; Palma, Alejandra; Tarifeño-Saldivia, Estefanía; Timmermann, Aline; Seifert, Gerald; Caprile, Teresa; Steinhäuser, Christian; García-Robles, María Angeles (Frontiers in Cellular Neuroscience, 2018)
Tanycytes are hypothalamic radial glia-like cells that form the basal wall of the third ventricle (3V) where they sense glucose and modulate neighboring neuronal activity to control feeding behavior. This role requires the coupling of hypothalamic cells since transient decreased hypothalamic Cx43 expression inhibits the increase of brain glucose-induced insulin secretion. Tanycytes have been postulated as possible hypothalamic neuronal precursors due to their privileged position in the hypothalamus that allows them to detect mitogenic signals and because they share the markers and characteristics of neuronal precursors located in other neurogenic niches, including formation of coupled networks through connexins. Using wild-type, Cx30-/-, and Cx30-/-,Cx43fl/fl:GFAP-Cre (dKO) transgenic mouse lines, we demonstrated that tanycytes are highly coupled to each other and also give rise to a panglial network specifically through Cx43. Using the hGFAP-EGFP transgenic mouse line, we provided evidence that the main parenchymal-coupled cells were astrocytes. In addition, electrophysiological parameters, such as membrane resistance, were altered when Cx43 was genetically absent or pharmacologically inhibited. Finally, in the dKO mouse line, we detected a significant decrease in the number of hypothalamic proliferative parenchymal cells. Our results demonstrate the importance of Cx43 in tanycyte homotypic and panglial coupling and show that Cx43 function influences the proliferative potential of hypothalamic cells.